How do companies with different life cycles respond to carbon trading?—Analysis of the moderating role of government subsidies - Guo, Xiaoxu; Zhang, Yue (Frontiers in Environmental Science, 2024)
Enterprises with diverse life cycles possess distinct survival and operational laws. Hence, it is crucial to comprehend whether all these enterprises can proficiently engage in green innovation under the guidance of carbon emissions trading (CET). This study leverages the quasi-natural experiment of CET policy, employing panel data encompassing A-share listed companies in Shanghai and Shenzhen spanning from 2008 to 2020. Through the application of the triple difference model, the research examines the influence of CET policy on the green innovation endeavors of enterprises characterized by various life cycles. The research outcomes reveal the following: 1) CET policy significantly impacts the green innovation of mature enterprises, and contributes to the enrichment of the quality of their green innovation endeavors. 2) Due to limitations pertaining to financing constraints and business expansion, CET policy fails to foster green innovation within the growth and decline phases of enterprises. 3) Government subsidies can overturn the unfavorable position of growth-stage enterprises in carbon emissions trading and propel them towards heightened green innovation. However, government subsidies do not yield a substantial moderating effect on the green innovation endeavors of maturity-stage enterprises. Simultaneously, even if declining-phase enterprises are subjected to government subsidies, these subsidies do not reverse their innovation disadvantage in carbon emissions rights trading. In addition, we also found that in areas with heightened public awareness of environmental protection and state-owned enterprises, the positive regulatory effect of government subsidies is more significant. The findings derived from this study bestow invaluable insights for decision-makers striving to optimize the implementation of the CET policy and effectively allocate government subsidies.